2021
DOI: 10.17350/hjse19030000209
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of Graphene Nanoplatelet-Coated TiB2 Reinforced AZ91 Magnesium Matrix Semi-Ceramic Hybrid Composites

Abstract: R ecent environmental protection policies focus on the need to reduce the weight of vehicles in order to increase fuel efficiency and reduce the impact of greenhouse gases emission [1]. Magnesium stands out as the structural metal in cases where weight reduction is important for materials used in industry and vehicles [2]. Low density, good strength to weight ratio, better heat dissipation, acceptable damping capacity, machinability, and recyclability make magnesium a much more attractive structural metal comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…On the other hand, it has been reported that adding nanosized ceramic reinforcements to magnesium and its alloys (such as Al 2 O 3 , ZrO 2 , or ZnO) resulted in an increase in both the material's overall strength and ductility [14,15]. Stir casting isutilized to manufacture magnesium matrix composites [16][17][18][19][20][21][22]. These composites use silicon-carbide-reinforced particles.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been reported that adding nanosized ceramic reinforcements to magnesium and its alloys (such as Al 2 O 3 , ZrO 2 , or ZnO) resulted in an increase in both the material's overall strength and ductility [14,15]. Stir casting isutilized to manufacture magnesium matrix composites [16][17][18][19][20][21][22]. These composites use silicon-carbide-reinforced particles.…”
Section: Introductionmentioning
confidence: 99%
“…Özellikle magnezyum matrisli kompozit malzemelerin korozyon dayanımı hakkında yapılan çalışmalar son derece sınırlıdır (Fink, 2003, Hassan and Gupta, 2002, Nguyen and Gupta, 2010, Aydogmus, 2015, Esen, 2012, Kelen et. al., 2018, Kelen vd., 2019, 2021b, Çevik et. al.…”
unclassified